Pengaruh Kompetensi, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Thamrin Brothers A.Rivai Palembang - Ika Rakhmalina (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This research entitled The Effect of Competence, Motivation and Organizational Commitment on Employee Performance of PT. Thamrin Brothers A. Rivai Palembang. The results of hypothesis testing through the F test (Simultaneous) using a confidence level of 90%, show that there is a significant influence of competence, motivation and organizational commitment together on the performance of the employees of PT. Thamrin Brothers A. Rivai Palembang. Quantitative analysis model using multiple linear regression analysis tools. The results of hypothesis testing through the t test (partial) show that there is a partially significant effect of competence on employee performance, there is a partially significant influence of motivation on employee performance and there is a partially significant effect of organizational commitment on the performance of employees of PT. Thamrin Brothers A. Rivai Palembang. The coefficient of determination test results prove that competence, motivation, and organizational commitment are able to contribute 91.0% in explaining changes that occur in employee performance. The researcher gave the first suggestion that PT. Thamrin Brothers A. Rivai Palembang, is expected to improve competence so that employees can optimally achieve a company goal including knowledge, understanding, abilities, values, attitudes, and interests. Second, leaders are expected to improve motivation to improve things including: work environment, fair and competitive wages, incentives and a sense of security at work. Third, leadership is expected to increase organizational commitment by including: justice and support, shared values, trust, organizational understanding, and employee involvement.